Remote Patient Identification based on ECG and Heart Beat Pattern over Wireless Channel - Garg, Neeraj; Lather, Jagdeep S; Dhurandher, Sanjay K (International Journal of Integrated Engineering, 2019)
Wireless Body Area Network (WBAN) is an innovative solution for distant monitoring of patients. In WBAN sensors are placed on human body to monitor vital parameters, and these parameters send to physician using wireless network. As in wireless network data is aggregated before transmission therefore when data is de-aggregated on receiver side it is important to know which data belongs to particular patient. In this work, it is shown that electrocardiogram (ECG) and heart beat pattern itself can be used for the identification of patient as it carries distinctive features which are unique to each person. Moreover, ECG is an image thus when transferred over Orthogonal Frequency Division Multiplexing (OFDM) wireless channel adds noise, therefore a level of Signal-to-Noise Ratio (SNR) needs to be maintained for error free recovery. This paper proposes ECG and heart beat pattern based patient identification process over OFDM channel. Proposed methodology is tested on ECG database and it has been found that the accuracy of the method is 99.98%.